Profesionalisme Guru Ditinjau dari Peraturan Menteri Pendidikan, Kebudayaan, Riset, dan Teknologi Republik Indonesia Nomor 19 Tahun 2024 Tentang Pendidikan Profesi Guru - Rustandi, Roni; Alinurdin; Koimah, Siti Mariyatul (Fakultas Keguruan dan Ilmu Pendidikan Universitas Pamulang, 2025)
Teacher professionalism issues include competence disparity, adaptation to pedagogical changes, welfare, distribution, and technological demands. This community service aimed to improve teachers’ and alumni’s understanding of becoming professional educators based on Permendikbudristek Regulation No. 19/2024. The method used was an online socialization involving 497 participants from various universities. Activities were conducted in three stages: planning, implementation, and evaluation. Results show improved understanding and active engagement in discussion. In conclusion, this activity effectively raised awareness and comprehension of the new professional teacher education regulation, contributing to the formation of professional teachers.